A neurochemical map of the developing amphioxus nervous system - Candiani, Simona (BioMed Central, 2012)
BACKGROUND: Amphioxus, representing the most basal group of living chordates, is the best available proxy for the last invertebrate ancestor of the chordates. Although the central nervous system (CNS) of amphioxus comprises only about 20,000 neurons (as compared to billions in vertebrates), the developmental genetics and neuroanatomy of amphioxus are strikingly vertebrate-like. In the present study, we mapped the distribution of amphioxus CNS cells producing distinctive neurochemicals. To this end, we cloned genes encoding biosynthetic enzymes and/or transporters of the most common neurotransmitters and assayed their developmental expression in the embryo and early larva. RESULTS: By single and double in situ hybridization experiments, we identified glutamatergic, GABAergic/glycinergic, serotonergic and cholinergic neurons in developing amphioxus. In addition to characterizing the distribution of excitatory and inhibitory neurons in the developing amphioxus CNS, we observed that cholinergic and GABAergic/glycinergic neurons are segmentally arranged in the hindbrain, whereas serotonergic, glutamatergic and dopaminergic neurons are restricted to specific regions of the cerebral vesicle and the hindbrain. We were further able to identify discrete groups of GABAergic and glutamatergic interneurons and cholinergic motoneurons at the level of the primary motor center (PMC), the major integrative center of sensory and motor stimuli of the amphioxus nerve cord. CONCLUSIONS: In this study, we assessed neuronal differentiation in the developing amphioxus nervous system and compiled the first neurochemical map of the amphioxus CNS. This map is a first step towards a full characterization of the neurotransmitter signature of previously described nerve cell types in the amphioxus CNS, such as motoneurons and interneurons.